PTU-010 Prevalence and phenotype of IBD across primary and secondary care: implications for colorectal cancer surveillance. (8th June 2018) - Hamilton, Benjamin; Heerasing, Neel; Hendy, Peter J; Moore, Lucy; Walker, Gareth J; Bewshea, Claire; Ahmad, Tariq; Goodhand, James R; Kennedy, Nicholas A
Abstract : Introduction: Patients diagnosed with colonic IBD have increased risk of colorectal cancer (CRC). Colonoscopic surveillance reduces the risk of CRC-associated death through early detection; national/international guidelines recommend chromoendoscopy. We aimed to assess the burden of IBD in primary care unknown to our service and to identify patients eligible for surveillance. Methods: We conducted a population-based observational study across primary and secondary care to evaluate the incidence/prevalence of IBD in our catchment. We identified cases from primary care using searches of practice databases and in secondary care using searches of hospital records. Case inclusion required a specialist diagnosis of ulcerative colitis (UC), Crohn's disease (CD) or IBD unclassified. IBD was phenotyped according to the Montreal Classification and patients under the age of 75 years, who had been diagnosed with IBD with colonic disease involvement for more than 10 years, were deemed eligible for colonoscopic surveillance. Results: Patients from 48/49 GP practices within our catchment were included. We identified 3690 patients with IBD living within our catchment of which 12% (875/3, 690) were unknown to any local secondary care service. Overall, UC prevalence was 453/100 000 people (95% confidence interval 433–474), Crohn's disease prevalence was 311/100 000 (95% CI 293–327), and IBD unclassified prevalence was 44/100 000 (95% CI 38–51). Patients managed solely in primary care, compared with those in secondary care, were older (mean age 60.9 vs 56.2 years, p<0.0001) and had longer disease duration (20.3 vs 14.2 years, p<0.0001). The proportion of UC out of total IBD was higher in primary care (69% vs. 58%, p<0.0001). A higher proportion of IBD patients in primary care than secondary care had undergone a colectomy (17% vs 5%, p<0.0001). Overall, 13% (388/2, 815) patients known to secondary care and 29% (257/875) of patients unknown to any secondary care services were eligible for colonoscopic surveillance, equivalent to approximately one colonoscopy list per week. Conclusions: We report one of the highest prevalence rates of IBD in Western Europe (1 in 124 patients). 12% of patients living in our immediate catchment area were unknown to our service; a third of these were eligible for colonoscopic colorectal cancer surveillance. Effective colorectal cancer surveillance programmes in IBD must target primary-care populations and not just known secondary care populations.